Micropopagation of Cryptocarya massoy (Oken) Kosterm. Trough Optimizing Callus Induction with Benzylaminopurine (BAP) Supplementation - Hanafi, Muhammad; Noli, Zozy Aneloi; Idris, M.; Hany, Iga Permata (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to evaluate the effect of BAP concentrations on explant response and callus formation in Massoia. The experiment was arranged in a Completely Randomized Design (CRD) with three BAP concentrations: 0.5 mg/L, 1.0 mg/L, and 1.5 mg/L, each with 24 replications. The culture medium used was Murashige and Skoog (MS), and observations were carried out for 7 days after planting. Parameters observed included the percentage of viable explants, browning, contamination, average callus formation, callus color, and texture. Data were analyzed using analysis of variance (ANOVA) at a 5% significance level. The results showed that 0.5 mg/L BAP yielded the highest explant survival rate (54%), the lowest browning rate (13%), and 35% contamination. Meanwhile, 1.5 mg/L BAP produced the highest average callus formation (0.21) with compact texture and brown coloration. Although not statistically significant, BAP concentrations affected explant viability and callus formation. A concentration of 0.5 mg/L tended to be optimal for maintaining explant viability, while 1.5 mg/L was more effective in inducing callus. These findings provide a preliminary basis for optimizing Massoia tissue culture techniques.